Pulmonary diffusing capacity as a predictor of performance in competitive swimming - Miller, R. L.; Robison, E.; McCloskey, J. B.; Picken, J. (The Journal of Sports Medicine and Physical Fitness, 1989)
The relationship between competitive swimming performance and lung function was assessed. Ohio State University varsity swimmers (N = 22) served as subjects. In this highly selective group it may be very difficult to detect small differences in variability. The following were found. - Swimming performance cannot be predicted on the basis of lung diffusing capacity. - In this selective swimming group lung function is greater than that of non-swimmers of the same age and height. - One season of intense training does not affect lung volume or gas exchange. - Heavy swimming training in physically mature persons does not influence lung diffusing capacity. Implication: The findings of this study should not be generalized to swimmers still in their growth phase, nor a more disparate group of individuals. It is not known if one of the selection factors for this superior group of swimmers was their above average lung function.